A Case of Laboratory-Acquired Murine Typhus - Woo, Jun Hee (Korean J Intern Med, 1990)
We encountered a 32-year-old Korean woman who developed murine typhus in a laboratory. She worked as a technician in a laboratory for rickettsial disease. Immunofluorescence test with rickettsial antigen (R. typhi) was positive at 1 : 320 on admission and 1 : 1280 after 4 weeks. A dose of 200 mg of doxycycline for 7 days proved to be effective for her condition.